Aptamer‐affinity column clean‐up coupled with ultra high performance liquid chromatography and fluorescence detection for the rapid determination of ochratoxin A in ginger powder. Issue 7 (3rd March 2014) - Yang, Xihui; Kong, Weijun; Hu, Yichen; Yang, Meihua; Huang, Luqi; Zhao, Ming; Ouyang, Zhen
<x xml:space="preserve">Abstract</x> Aptamers are single‐stranded oligonucleotides with high affinity and specificity and are widely used in targets separation and enrichment. Here, an aptamer‐affinity column (AAC) was firstly prepared in‐house through a covalent immobilization strategy. Then, ochratoxin A (OTA) in ginger powder was absorbed and enriched using the new aptamer‐based clean‐up technology for the first time, and was further analyzed by ultra high performance liquid chromatography with fluorescence detection. After optimization, the average recoveries for blank samples spiked with OTA at 5, 15, and 45 μg/kg ranged from 85.36 to 96.83%. Furthermore, the AAC exhibited a similar accuracy as an immunoaffinity column to clean up OTA in ginger powder. Above all, it exhibited better reusability, twice that of the immunoaffinity column, had lower toxicity and cost, and took less time. Of 25 contaminated ginger powder samples, OTA contamination levels ranged from 1.51 to 4.31 μg/kg, which were lower than the European Union (EU) regulatory limits. All the positive samples were further confirmed by ultra‐fast LC with MS/MS. In conclusion, the method of clean‐up based on the AAC coupled to ultra‐HPLC with fluorescence detection was rapid, specific, and sensitive for the quantitative analysis of OTA in a complex matrix.